2020
DOI: 10.1021/acs.jced.0c00389
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate Stability Conditions of CO2 + TBPB + Cyclopentane + Water System: Experimental Measurements and Thermodynamic Modeling

Abstract: The current study provides experimental data and thermodynamic modeling of hydrate stability conditions of CO2 + tetra n-butylphosphonium bromide (TBPB) + cyclopentane (CP) + water system. The experimental results are presented from (288 to 292) K and (1.45 to 3.30) MPa at 0.10, 0.15, 0.17, and 0.20 mass fractions of TBPB in aqueous solutions. To measure the experimental data, an isochoric step-heating pressure-search method was applied. The validity of the method used in the current study was evaluated by reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…MeOH exhibited the best performance as an inhibitor. 48 Mohammadi et al experimentally observed that using the mixture of TBPB + cyclopentane promoter in the water + CO 2 system could increase the hydrate stability temperatures by 12 K. 49 Mayoufi et al used differential scanning calorimetry (DSC) method to evaluate the phase behavior of TBPB and TBPB + CO 2 semiclathrate hydrates. 50 According to their results, the formation pressure at 286 K decreased from 3.5 to 0.5 MPa with increasing promoter concentration from 0 to 0.0058 mole fraction.…”
Section: Theory and Backgroundmentioning
confidence: 99%
“…MeOH exhibited the best performance as an inhibitor. 48 Mohammadi et al experimentally observed that using the mixture of TBPB + cyclopentane promoter in the water + CO 2 system could increase the hydrate stability temperatures by 12 K. 49 Mayoufi et al used differential scanning calorimetry (DSC) method to evaluate the phase behavior of TBPB and TBPB + CO 2 semiclathrate hydrates. 50 According to their results, the formation pressure at 286 K decreased from 3.5 to 0.5 MPa with increasing promoter concentration from 0 to 0.0058 mole fraction.…”
Section: Theory and Backgroundmentioning
confidence: 99%
“…1,10,11 To overcome these inconveniences, different types of chemicals (soluble or nonsoluble in water) have been added to the system for controlling the hydrate formation or dissociation conditions. These additives are divided into two different types: (1) thermodynamic promoters for controlling the temperature and pressure 12,13 and (2) kinetic promoters for affecting the acceleration rate of hydrate formation. 7,12,14−17 Scientists have recently found that additives such as DX act like a thermodynamic promoter and kinetic promoter simultaneously, with the capability of solving the previous shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these inconveniences, different types of chemicals (soluble or nonsoluble in water) have been added to the system for controlling the hydrate formation or dissociation conditions. These additives are divided into two different types: (1) thermodynamic promoters for controlling the temperature and pressure , and (2) kinetic promoters for affecting the acceleration rate of hydrate formation. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Hydrate-based separation (HBS) is one of the most promising processes for enhancing CO 2 separation [6]. This method is based on the fact that the hydrate phase equilibrium conditions of CO 2 are moderate [7].…”
Section: Introductionmentioning
confidence: 99%